The Meiofaunal Diversity in Progo and Opak River Estuaries - Suwartiningsih, Nurul; Muhammad Ardhi, Fauzan (Journal of Biotechnology and Natural Science, 2021)
The Estuaries of Progo and Opak rivers, being the terminus of all rivers flowing through the Special Region of Yogyakarta, are highly susceptible to pollution which results in decreased water quality. The use of meiofauna as a bioindicator to assess water quality in the estuaries of Progo and Opak rivers has never been made. This study aims to determine the diversity of meiofauna at the estuaries of Progo and Opak rivers. Stations and sampling points are determined using purposive sampling method. Extraction is conducted using water ice treatment method. The meiofauna obtained from the sediment screening are then identified, calculated and analyzed to find out the index values ​​of abundance, dominance, diversity, and evenness. The results showed that the highest meiofauna abundance index was 247,333 ind. m-2 at the estuary of Progo river station 1 at the time of the first pick-up. While the lowest meiofauna abundance was 13,333 ind. m-2 at station 2 of Opak river estuary during the first take. The dominance at the estuaries of Progo and Opak rivers is in the moderate category. The meiofauna diversity in both river estuaries is categorized as low to moderate. Evenness in both estuaries is uneven at several stations. The meiofauna diversity at the estuaries of Progo and Opak rivers is low to moderate, although the water quality still meets the quality standards.